COVID-19 OUTBREAK AND ROLE OF TOURISM DEVELOPMENT ON ECONOMIC GROWTH IN PAKISTAN - Abdul Latip, Normah; Karim, Rehmat; Marzuki, Azizan; Muhammad, Faqeer; Shah, Attaullah; Yilret Nanle, Veronica; Umar, Mohd Umzarulazijo (PLANNING MALAYSIA, 2021)
The current research aimed to find out the effect of tourism development on economic growth in Pakistan for the period (1995 to 2017) by using Canonical Regression Analysis (CCR) and Dynamic Least Square (DOLS) method. In addition, a unit root test is used to find out the static nature of the variables, and for the robust check, the authors utilize the Fully Modified Least Square (FMOLS) method. The results of the CCR and DOLS shows the key role of tourism development on growth, and FMOLS confirms these findings. In addition, the contribution of financial development is insignificant and positive. However, inflation harms economic growth, which depicts that the government of Pakistan will face severe challenges to achieve the targeted level of growth in future. In addition, an outbreak of Coronavirus Disease (Covid-19) is another challenge that will cause a significant decline in tourism receipts.